Epigenetics Regulation in Responses to Abiotic Factors in Plant Species: A Systematic Review - Geane Santos da Costa; Amanda Freitas Cerqueira; Carolina Reis de Brito; Marcelo Schramm Mielke; Fernanda Amato Gaiotto (Plants, 2024)
Plants have several mechanisms to adapt or acclimate to environmental stress. Morphological, physiological, or genetic changes are examples of complex plant responses. In recent years, our understanding of the role of epigenetic regulation, which encompasses changes that do not alter the DNA sequence, as an adaptive mechanism in response to stressful conditions has advanced significantly. Some studies elucidated and synthesized epigenetic mechanisms and their relationships with environmental change, while others explored the interplay between epigenetic modifications and environmental shifts, aiming to deepen our understanding of these complex processes. In this study, we performed a systematic review of the literature to analyze the progression of epigenetics studies on plant species’ responses to abiotic factors. We also aimed to identify the most studied species, the type of abiotic factor studied, and the epigenetic technique most used in the scientific literature. For this, a search for articles in databases was carried out, and after analyzing them using pre-established inclusion criteria, a total of 401 studies were found. The most studied species were Arabidopsis thaliana and Oryza sativa, highlighting the gap in studies of non-economic and tropical plant species. Methylome DNA sequencing is the main technique used for the detection of epigenetic interactions in published studies. Furthermore, most studies sought to understand the plant responses to abiotic changes in temperature, water, and salinity. It is worth emphasizing further research is necessary to establish a correlation between epigenetic responses and abiotic factors, such as extreme temperatures and light, associated with climate change.